PORTRAIT OF STUDENTS’ MISCONCEPTIONS USING FOUR-TIER MULTIPLE CHOICE DIAGNOSTIC TEST ON ROTATIONAL DYNAMICS MATERIAL IN CLASS XI SENIOR HIGH SCHOOL - Lubis, Salsabila Khairusysyifa; Bunawan, Wawan (Universitas Negeri Medan, 2024)
Misconception is a mismatch between the understanding of the concept known by students and the actual concept. Physics is a science that has several concepts. The profile of misconceptions on physics concepts must be identified so that students have an appropriate understanding of the concepts. The purpose of this research is to analyze students’ concept understanding and misconceptions of Rotational Dynamics material using a four-tier multiple choice diagnostic test. The type of research used is descriptive with qualitative and quantitative approaches. This research was conducted in one of the high schools in Medan in Grade XI IPA. The population in this research was grade XI students majoring in IPA. The research sample was obtained by using purposive sampling technique as many as 64 students of grade XI IPA 2 and XI IPA 3. Sampling based on certain criteria from population participants. The criteria are classes whose students have finished learning Rotational Dynamics material and have not been tested on Rotational Dynamics material. Data collection techniques in the form of diagnostic tests response questionnaires and interviews. The test used is a four-tier multiple choice diagnostic test that has been validated by experts. The diagnostic test consists of 18 valid items with a reliability of 0.912 including a very high category, good differentiating power, and moderate difficulty level. The results showed that students' concept understanding of Rotational Dynamics material was categorized as moderate with 44.88% of students understood the concept, 50.17% of students had misconceptions, and 4.95% of students did not understand the concept, and students' responses to the use of four-tier multiple choice diagnostic tests obtained 80% with good criteria.